Utilizing Financial Technology, Financial Literacy, and Financial Self-Efficacy in Achieving Generation Zoomer’s Financial Inclusion - Zusrony, Edwin; Anzie, Luthfy Purnanta; Manalu, Gibson; Permana, Ivan; Asti, Pindo; Imaliya, Tri (Universitas Bumigora, 2024)
Economic development in the digital era is very rapid, which also encourages people to gain access to financial product services called financial inclusion. The growing population in Indonesia, which is dominated by generation Z, makes financial inclusion very important for those of productive age. This research aims to determine the influence of financial technology, financial literacy and financial self-efficacy on financial inclusion. The population is generation Z in the city of Semarang, a total of 60 respondents taken using purposive sampling techniques. Data collection uses a questionnaire with Likert scale parameters. The data analysis technique uses multiple linear regression and is processed using SPSS version 29 software. Research findings show that the variables financial technology, financial literacy and financial self-efficacy have a positive and significant influence on financial inclusion. Based on these findings, it shows that the better the knowledge related to financial technology, financial literacy and financial self-efficacy, the better the financial inclusion will be.